Preparation of activated carbon from water hyacinth stems by chemical activation with K2CO3 and its performance as adsorbent of sodium naproxen - González‐García, P.; Gamboa‐González, Sheila; Andrade Martínez, Irving; Hernández‐Quiroz, Teresa (Environmental progress & sustainable energy, 2020)
Activated carbons were obtained from water hyacinth stems using K2CO3 as activation agent, varying the impregnation time and the activation temperature and time, accordingly to a 23 factorial experimental design. The produced carbons showed activation yields (8–20%), alkaline point of zero charge (average of 9.5), methylene blue indexes from 264 to 893 m2/g, carboxylic surface groups in major proportion and graphitization degree from 4.01 to 6.27%. According to the statistical analysis, the activation temperature was significant for the yield and the methylene blue index. Activated carbon, labeled as AC5, was selected to assessing the naproxen adsorption in aqueous solution. Batch experiments yielded maximum adsorption capacity of 77.44% at pH ≈ 10.3, and contact time of 8 hr at initial concentration of 40 mg/g. The adsorption kinetics, isotherm model, and diffusion mechanism were described by the pseudo‐second order model, the Redlich‐Peterson equation and the film diffusion, respectively.